1996
DOI: 10.1002/(sici)1097-0290(19960720)51:2<190::aid-bit8>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Control of glycolytic flux inZymomonas mobilis by glucose 6-phosphate dehydrogenase activity

Abstract: Glycolytic genes in Zymomonas mobilis are highly expressed and constitute half of the cytoplasmic protein. The first four genes (glf, zwf, edd, glk) in this pathway form an operon encoding a glucose permease, glucose 6‐phosphate dehydrogenase (G6‐P dehydrogenase), 6‐phosphogluconate dehydratase, and glucokinase, respectively. Each gene was overexpressed from a tac promoter to investigate the control of glycolysis during the early stages of batch fermentation when flux (qCO2) is highest. Almost half of flux con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The Entner-Doudoroff pathway used by Z. mobilis for catabolism can be affected by changes in the redox balance at both glucose-6-phosphate dehydrogenase and glyceraldehyde-3-phosphate dehydrogenase. Snoep et al [27] found that the flux of glycolysis in Z. mobilis is limited by the activity of glucose-6-phosphate dehydrogenase, both during normal operation of the Entner-Doudoroff pathway (Figure 6) and when the organism is exposed to an excess of ethanol. An increased intracellular concentration of NAD + due to acetaldehyde addition would be predicted to increase glucose-6-phosphate dehydrogenase activity and also augment glyceraldehyde-3-phosphate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Entner-Doudoroff pathway used by Z. mobilis for catabolism can be affected by changes in the redox balance at both glucose-6-phosphate dehydrogenase and glyceraldehyde-3-phosphate dehydrogenase. Snoep et al [27] found that the flux of glycolysis in Z. mobilis is limited by the activity of glucose-6-phosphate dehydrogenase, both during normal operation of the Entner-Doudoroff pathway (Figure 6) and when the organism is exposed to an excess of ethanol. An increased intracellular concentration of NAD + due to acetaldehyde addition would be predicted to increase glucose-6-phosphate dehydrogenase activity and also augment glyceraldehyde-3-phosphate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%